A Coupled Electrochemical-Thermal Failure Model for Predicting the Thermal Runaway Behavior of Lithium-Ion Batteries. Issue 16 (1st January 2018) - Feng, Xuning; He, Xiangming; Ouyang, Minggao; Wang, Li; Lu, Languang; Ren, Dongsheng; Santhanagopalan, Shriram
Abstract : Thermal runaway is always a troublesome problem that hinders the safe application of high energy lithium-ion batteries. There is an urgent need to interpret the voltage and temperature changes and their underlying mechanisms during thermal runaway, in order to guide the safe design of a battery system. This paper is dedicated to building a coupled electrochemical-thermal model that can well predict the voltage drop and temperature increase during thermal runaway. The model can capture the underlying mechanism of ① the capacity degradation under high temperature; ② the internal short circuit caused by the thermal failure of the separator; and ③ the chemical reactions of the cell components that release heat under extreme temperature. The model is validated using by experimental data, therefore the modeling analysis has high fidelity. We employ the model to analyze 1) the capacity degradation under extreme temperature; 2) the influence of the SEI decomposition and regeneration on the thermal runaway behavior; 3) the heat generation by internal short circuit in the thermal runaway process. The discussions presented here help extend the usage of lithium-ion batteries at extreme high temperature (>80°C), and guide the safe design of lithium-ion batteries with less hazard level during thermal runaway.